The Long-Term Outcome Comparison of Different Time-Delayed Kallikrein Treatments in a Mouse Cerebral Ischemic Model - Yaohui Ni; Kefu Cai; Yujie Hu; Chuan-hui Wang; Yuanyuan Zhang; Hua Huang; Xing Su; Jin-hua Gu (Stem Cells International)
Delayed administration of kallikrein after cerebral infarction can improve neurological function. However, the appropriate kallkrein treatment time after ischemic stroke has not been illuminated. In this study, we compared the long-term outcome among three kallikrein therapeutic regimens starting at different time points following mouse cerebral ischemia. Furthermore, the protective mechanisms involving neurogenesis, angiogenesis, and AKT-GSK3β-VEGF signaling pathway were analyzed. Human tissue kallikrein was injected through the tail vein daily starting at 8 h, 24 h, or 36 h after right middle cerebral artery occlusion (MCAO) until the 28th day. Three therapeutic regimens all protected against neurological dysfunction, but kallikrein treatment starting at 8 h after MCAO had the best efficacy. Additionally, kallikrein treatment at 8 h after MCAO significantly enhanced cell proliferation including neural stem cell and induced differentiation of neural stem cell into mature neuron. Kallikrein treatment starting at 8 h also promoted more angiogenesis than other two treatment regimens, which was associated with AKT-GSK3β-VEGF signaling pathway. Thus, we confirm that three delayed kallikrein treatments provide protection against cerebral infarction and furthermore suggest that kallikrein treatment starting at 8 h had a better effect than that at 24 h and 36 h. These findings provide the experimental data contributing to better clinical application of exogenous kallikrein.